Reconstruction of the middle hepatic vein using a vein graft from the resected portion of the liver - ShiWei Yang; DongDong Han; Liang Wang; Lei Gong; CanHong Xiang (Surgical Case Reports, 2020)
Abstract Background The middle hepatic veins are often infiltrated by intrahepatic cholangiocarcinoma. Reconstruction of the hepatic vein plays a critical role in preserving more of the residual liver volume and reducing the risk of postoperative liver failure in extreme hepatectomy. We here report a novel way to reconstruct middle hepatic vein by using vessel grafts from wasted liver. Case presentation Case 1: A 64-year-old man was diagnosed with intrahepatic cholangiocarcinoma. The bifurcation and left branch of the portal vein were stenosed, and the root of the middle hepatic vein was infiltrated by the tumor. An extended left hepatectomy was performed, the portal vein was resected and reconstructed, and the middle hepatic vein was reconstructed by anastomosing the proximal left hepatic vein to the distal middle hepatic vein. Case 2: A 69-year-old woman was diagnosed with intrahepatic cholangiocarcinoma. The tumor was located in the left lobe of the liver and the left and middle hepatic veins were infiltrated by the tumor. An extended left hepatectomy was performed, and the left portal vein was used as a vein graft to reconstruct the middle hepatic vein. Both of the two patients’ postoperative ultrasound showed vessel graft patency. Conclusion Using a vein graft from the resected portion of the liver to reconstruct the middle hepatic vein was a useful technique and showed good result.